„Sam nie wiem, co robić, bo mi go żal”. Dziecięce autobiografie opiekuńcze - Marta Rakoczy (Autobiografia, 2024)
In the text, applying the Spyros Spyrou’s perspective of critical childhood studies, I interpret the care book of Icek - an interwar pupil of the Orphanage of Janusz Korczak/Henryk Goldszmit and Stefania Wilczynska. Exploring the historical politics of constructing the voices and genres of children's narratives, I emphasize the peculiarity of Icek's care autobiography as a form of reclaiming children's agency. Icek's caregiving autobiography is not, of course, an autobiography if we recognize autobiographies with the possibility of self-expression: the expression of the voice of the authentic self, which can only be empathically understood if it "sincerely" manifests personal or intimate experiences in a public forum. In the text, I show that this account of agency, characteristic of many modern ideologies, is inadequate to understand Icek’s text. Agency, in his view, is an ecological action. It is not the property of a person or his actions, but a collectively produced ability to act empathetically in networks of social relations. It represents not so much a voice as a statement on an issue that concerns the community. It is built in relationship with it, through constant communication with it, translating into real actions taken on behalf of oneself and others.